Antibacterial Activities of Soaps Prepared from Selected Plant Oils - Warra, A.A.; Tanko, H.Y.; Salisu, N.; Isah, K.; Adedara, A.O. (International Journal of Scientific Research in Biological Sciences, 2020)
Plant oils are liquids extracted from plants usually plant seeds. They can be obtained through steam-distillation, solvent-extraction, resin trapping, and mechanical method such as cold pressing. Plant oil constituents contribute to the beneficial or adverse effects against pathogenic bacteria because the skin harbors diverse bacteria, and alterations to these bacteria can affect the effectiveness of skin as a blockage to infectious disease or create skin injury. Soaps formulated with plant oil have been found effective both in cleaning and killing bacteria. The aim of this study is to determine the antibacterial activity of some selected seed oil from plant for soap formulation. Soap tablets were produced through the cold saponification process by reacting to the selected seed oils (baobab oil, canary oil, castor beans oil, wild grapes, cottonseed oil, onion oil, and calabash seed oil) with sodium hydroxide. The sodium hydroxide solution was added to each seed oils in ratio 1:1 v/v and activities of the soap against Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli, and Salmonella typhi were investigated. The results revealed that soap formulated with Onion seed oil possessed the highest activity against all bacterial strains. However, cottonseed oil, canary melon oil possessed good activities against all strains of bacteria only at higher concentrations (150mg/L and 200mg/L). The result suggests that the formulated soap especially those formulated with Onion seed oil, cottonseed oil, and canary melon oil will be effective in the eradication of skin bacteria. The oils can be used as an antibacterial agent in the industrial production soaps